Ionospheric studies of the solar eclipse 25 December, 1954 - McElhinny, M W (Rhodes University, Faculty of Science, Department of Physics, 1959)
Since the Kennelly- Heaviside hypothesis in 1902 of the existence of a partially conducting layer in the upper atmosphere was proved to be true by the experiments of APPLETON and BARNETT (1925) and BREIT and TUVE (1926), this region has become known as the ionosphere. The ionosphere was soon discovered to consist of, not one but several layers (Fig. 1) (i) A layer at a height of just over 100 km. called the E layer. (ii) A layer at a height of approximately 300km. called the Fâ‚‚ layer. (iii) A layer at a height of approximately 200 km. called the Fâ‚ layer; this layer differs from the other two in that it is only present during the day time in Summer. (iv) Occasional intense reflections from a height of about 100 km. are found - these cannot be attributed to the normal E layer and have received the name "Sporadic E". The presence of two E layers (Eâ‚ and Eâ‚‚) has been suggested by HALLIDAY (1936) and BEST and RATCLIFFE (l978) but until recently most workers still seem to attribute these reflections to Sporadic E. Recent measurement by rockets of the electron density at E layer heights still do not confirm whether such bifurcation exists in the E region. The diurnal and seasonal variations of the first three layers indicate that the sun is the chief agent in their production. It is generally agreed that these layers consist of ionised molecules or atoms and free electrons produced by radiation from the sun. The origin of Sporadic E ionisation is still obscure, but it is thought that these sudden increases in ionisation which occur in E layer heights are due to passing meteors. Recently it has also been suggested by SEDDON, PICKAR and JACKSON (1954) from rocket measurements that Sporadic E might be due to a steep electron density gradient above the B layer.
Keywords: Ionosphere -- Research; Solar eclipses